Allocation concealment, prediction and selection bias - Torgerson, David (Henry Stewart Talks, 2007)
Introduction to selection bias, Allocation methods, Evidence for subversion bias, Restricted or simple randomization, Problems with cluster randomization, Evidence for selection bias in cluster trials
Archived at 2018/05/31